Hate Speech Against Disabled Persons: A Forensic Analysis of Legal Framework in India and Beyond - Suvidutt M.S; Aditya Tomer (Indian Journal of Forensic Medicine & Toxicology, 2022)
Hate Speech is a social menace. Disability hate speech is nothing but hatred perpetuated against any disabled person. It is prevalent offline as well as on the virtual platform. Despite the legal provisions against hate speech, instances of hate speech are increasing rapidly. There are many developed countries such as the US, UK or Australia that have specialized laws and machinery at place to regulate speech towards the persons with disabilities. However, India lags behind in framing policies or enacting laws, be it protecting the interest of disabled persons against hate speech or hate crime perpetuated against them. Amidst pandemic, discrimination and untold miseries faced by disabled individuals mount day by day, in real world as well as virtual world. In these challenging times, there is a need to check as to what are the laws in India that protect people with disabilities against hate speech. There is a need to analyze in a forensic perspective the remedies available for the victimized individuals with disability. This research paper further put forth various suggestions and means to improve protection of such persons with disabilities.